2012
DOI: 10.1080/13825585.2011.621930
|View full text |Cite
|
Sign up to set email alerts
|

Bingo! Externally supported performance intervention for deficient visual search in normal aging, Parkinson's disease, and Alzheimer's disease

Abstract: External support may improve task performance regardless of an individual’s ability to compensate for cognitive deficits through internally-generated mechanisms. We investigated if performance of a complex, familiar visual search task (the game of bingo) could be enhanced in groups with suboptimal vision by providing external support through manipulation of task stimuli. Participants were 19 younger adults, 14 individuals with probable Alzheimer’s disease (AD), 13 AD-matched healthy adults, 17 non-demented ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
(61 reference statements)
0
25
1
Order By: Relevance
“…Neither the younger nor older adults were affected by the contrast manipulation, which differs from Toner et al (2012) who found an effect of contrast. This difference between studies may be due to Laudate et al (2012) using a higher baseline visual contrast (62% Michelson contrast) than Toner et al (22% Michelson contrast). However, overall Laudate et al supports the information degradation hypothesis, in which a manipulation of visual acuity affected both older and younger adults’ task performance.…”
Section: 0 Information Degradation Hypothesis In Visual Searchmentioning
confidence: 76%
See 2 more Smart Citations
“…Neither the younger nor older adults were affected by the contrast manipulation, which differs from Toner et al (2012) who found an effect of contrast. This difference between studies may be due to Laudate et al (2012) using a higher baseline visual contrast (62% Michelson contrast) than Toner et al (22% Michelson contrast). However, overall Laudate et al supports the information degradation hypothesis, in which a manipulation of visual acuity affected both older and younger adults’ task performance.…”
Section: 0 Information Degradation Hypothesis In Visual Searchmentioning
confidence: 76%
“…In another study testing the information degradation hypothesis in visual search (Laudate et al, 2012), older and younger adults played bingo on a touch-screen computer presented under several visual conditions (This study also reported results for Alzheimer’s and Parkinson’s disease patients, not discussed here.). In order to ensure that the results were not due to age-differences in motor speed, the authors controlled for Purdue Pegboard (Lafayette Instrument, Lafayette, IL, United States) performance when appropriate.…”
Section: 0 Information Degradation Hypothesis In Visual Searchmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent work by Cronin-Golomb, Gilmore and their colleagues has provided some evidence that the performance of AD patients in tasks such as letter identification, word reading, picture naming, face discrimination, and digit cancellation (133) can be improved, sometimes to normal levels, simply by increasing the contrast of stimuli to compensate for their contrast sensitivity deficit (134136). In addition, enhancing the contrast or strength of visual stimuli may improve advanced AD patients’ activities of daily living, such as pill finding (137), playing Bingo (138), and eating (139). The positive impact of stimulus enhancement has been shown in patients who had been screened for visual acuity and major age-related vision problems, such as cataracts, glaucoma, and macular degeneration (133138).…”
Section: Visual System In Aging and Admentioning
confidence: 99%
“…In addition, enhancing the contrast or strength of visual stimuli may improve advanced AD patients’ activities of daily living, such as pill finding (137), playing Bingo (138), and eating (139). The positive impact of stimulus enhancement has been shown in patients who had been screened for visual acuity and major age-related vision problems, such as cataracts, glaucoma, and macular degeneration (133138). It is likely that the stimulus enhancement would not help patients with severe vision pathology.…”
Section: Visual System In Aging and Admentioning
confidence: 99%